INTERACTIVE LEARNING APPS FOR AUTISTIC KIDS - Muhammad Nizam, Shafiq Danial (IRC, 2019)
This Mobile application is created to help and assist autistic kids with problems in learning as to teach them to be able to communicate with social world. The learning module inside the application consists of 3 types of module which will help these socially impaired kids to be able to grasp the fundamentals of emotions, learning to speak confidently and also learn as part of their education. The autistic kids that are targeted in this application are autistic kids below the age of 12 in which is the most suitable. With the help of Agile methodology in which allows rapid changes to made, it gives an opportunity for autistic kids to learn better as they are easily bored as part of their nature. This application seeks to help improve the quality of life through education and human skills that these kids lack while also following the sets of academic requirements of the Bahan Bantuan Mengajar(BBM).